EPIKUREANISME DAN STOISISME DALAM THE AGE OF REASON KARYA JEAN PAUL SARTRE - Djoko Ardhityawan (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2007)
ABSTRACTThe Age of Reason is a novel which contains with philosophical elements. This Jean Paul Sartre’s novel is a work that shows equality between philosophy and literature. This novel also performs the existence of philosophy in literature instead of literature in philosophy. Based on the background of the study this thesis searches to find the philosophicalelements of epicureanism and stoicism in The Age of Reason novel. The purpose of the study works on identifying epicureanism elements, identifying stoicism elements and analyzing both elements in The Age of Reason novel. Epicureanism is defined as ‘pain avoiding’ to achieve happiness while stoicism is defined as ‘pain coping’ to solve lifeproblem. To reach the purpose of the study, the study focused on Mathieu as the main character of the novel by using the narration of his character and characterization in the process of achieving his maturity. By using descriptive qualitative research, the study centered on structural approach and content approach. Structural approach describes andanalyzes intrinsic elements of the novel, in this respect is narration and characterization aspects. The structural approach uses Stanzel’s theory of narration as the guidance. On the contrary the content approach is extrinsic approach used to identify and analyze Epicureanism and stoicism elements on Mathieu’s attitude in achieving his maturity. Thecontent approach is guided by existentialism theory, epicureanismand stoicism. Both structural approach and content approach equip each other to achieve the purpose of the study. By using ‘close reading’ technique both approaches can identify and analyze Epicureanism and stoicism in Mathieu’s attitude on his maturity process. Therefore, the existence of epicureanism and stoicism elements can beproved in The Age of Reason novel. In achieving his maturity, Mathieu seeks for his happiness by avoiding his problem. He wants to keep his engagement with his girl friend